1997
DOI: 10.1002/ejtc.55
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐ligand interactions of the Cu‐NO complex at the ground and low‐lying excited states: an ab initio MO study

Abstract: SUMMARYThe geometrical structure and vibrational modes of the complex formed between the copper atom and NO molecule for the ground state have been studied by means of an ab initio MO method. The ground and low-lying electronic states were determined by using the singly excited configuration interaction (CI) calculations. The bent structure with a Cu-N-O angle of 117• is obtained as the most stable form of the complex at the MP2/6-311G* level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Several theoretical and matrix-isolation studies on copper nitrosyls have been reported. These investigations have found that N-bound nitrosyls are more stable than O-bound nitrosyls and that the ground-state geometry for Cu−NO is bent while that for [Cu−NO] + is linear. Also, copper-containing zeolites have been found to form mono- and dinitrosyl species when exposed to NO. …”
Section: Group 11 Nitrosylsmentioning
confidence: 99%
“…Several theoretical and matrix-isolation studies on copper nitrosyls have been reported. These investigations have found that N-bound nitrosyls are more stable than O-bound nitrosyls and that the ground-state geometry for Cu−NO is bent while that for [Cu−NO] + is linear. Also, copper-containing zeolites have been found to form mono- and dinitrosyl species when exposed to NO. …”
Section: Group 11 Nitrosylsmentioning
confidence: 99%
“…30 The structure, stability and bonding of mononuclear copper mononitrosyl neutrals and cations have also been investigated with theory. [31][32][33][34][35][36][37] However, there is no experimental report on the spectroscopic study of copper nitrosyl cation complexes in the gas phase. In the present paper, mononuclear copper nitrosyl cation complexes [Cu(NO) n ] + (n = 1-5) and their argon tagging analogues are produced and studied by infrared photodissociation spectroscopy in the nitrosyl stretching region in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, the HOMO of CO 1c), we omitted discussion because the NO interaction with transition metal complex has been discussed well. 65,66 The ONIOM[MP4(SDQ):ωB97XD]-calculated binding energy (BE) of Mm−R−L decreases in the order CO > CO 2 > NO > N 2 , as shown in Table 1; the R substituent influences little their binding energies. In comparison with previous experimental and computational studies on the HKUST-1, 30,46,48,67 the binding energy is underestimated here, but the decreasing trend of the binding energy (CO > CO 2 > NO > N 2 ) is the same as that of the previous works, suggesting that the method employed here describes well the relative binding energy of gas molecule with Cu−OMS.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As a result, the Cu β –O–C angle becomes 117° and the Cu α –Cu β –O angle is 167° in the normal position. Although NO coordination structure is different from the CO coordination one (Figure c), we omitted discussion because the NO interaction with transition metal complex has been discussed well. , …”
Section: Resultsmentioning
confidence: 99%